2011
DOI: 10.1002/cbic.201100574
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Heterologous Expression of Three Type II PKS Gene Clusters from Streptomyces bottropensis

Abstract: Mensacarcin is a potent cytotoxic agent isolated from Streptomyces bottropensis. It possesses a high content of oxygen atoms and two epoxide groups, and shows cytostatic and cytotoxic activity comparable to that of doxorubicin, a widely used drug for antitumor therapy. Another natural compound, rishirilide A, was also isolated from the fermentation broth of S. bottropensis. Screening a cosmid library of S. bottropensis with minimal PKS-gene-specific primers revealed the presence of three different type II poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…The rishirilide biosynthetic gene cluster contains two luciferase-like monooxygenase genes [4]. Inactivation of rslO6 did not influence rishirilide production as described above.…”
Section: Galvaquinone a Is Produced By Mutants Lacking Rslo1mentioning
confidence: 66%
See 1 more Smart Citation
“…The rishirilide biosynthetic gene cluster contains two luciferase-like monooxygenase genes [4]. Inactivation of rslO6 did not influence rishirilide production as described above.…”
Section: Galvaquinone a Is Produced By Mutants Lacking Rslo1mentioning
confidence: 66%
“…Rishirilide biosynthesis is controlled by four regulatory genes (rslR1, rslR2, rslR3 and rslR4) that belong to the family of SARP-regulatory genes (rslR1 and rslR2), the family of LAL regulatory genes (rslR3) and the family of MarR transcriptional regulatory genes (rslR4), respectively [4]. We observed that S. albus J1074 containing cos4 and pUWL-H-rslR1 + rslR2 + rslR3 (pUWLR1R2R3) produced more rishirilide B than S. albus J1074 containing only cos4.…”
Section: Overexpression Of the Regulatory Genes Rslr1 Rslr2 And Rslrmentioning
confidence: 99%
“…GTRI‐02 is also produced by Streptomyces sp. strains GW4184, ANK313, and Gö C4/4, and recently was identified in Streptomyces violaceoruber and Streptomyces coelicolor A3(2) . According to a bio‐retrosynthetic analysis (using fungal biogenesis), 2 is synthesized chemoenzymatically by use of a fungal enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…[7,8] Therefore,w e compared the spectral and rotation data, and HPLC retention time,o fo ur synthetic (2R,3R,4R)-2 with those of natural (+ +)-2,w hich was kindly provided by Professor Dr.B echthold. [2] The 1 HNMR spectrum of our synthetic (2R,3R,4R)-2 matched that of natural (+ +)-2,but the optical rotation of the natural product had aplus sign [ a ½ 25 D ¼ + 46.7 (c 0.03, EtOH)], and the HPLC retention time of natural (+ +)-2 (t = 8.3 min) was different from that of our synthetic (2R,3R,4R)-2 (t = 11.2 min) on achiral-phase column (Figure 2a…”
Section: Communicationsmentioning
confidence: 99%
“…(À)-Rishirilide A( 1)a nd (+ +)-rishirilide B[ ( + +)-2]a re anthracenone-type natural products isolated from Streptomyces rishiriensis OFR-1056 in 1984 ( Figure 1), [1] and were subsequently found in Streptomyces bottropensis. [2] (+ +)-Rishirilide B[(+ +)-2]has moderate inhibitory activities against a 2macroglobulin, glutathione S-transferase,a nd asparaginyl-tRNAs ynthetase, [3,4] which play roles in thrombosis and cancer. Key structural features of the rishirilides include three or four consecutive stereogenic centers involving quaternary carbon centers on the Aring.…”
mentioning
confidence: 99%